Analisis Pertumbuhan Return On Investment (ROI) pada PT. Kino Indonesia Tbk Sebelum dan Sesudah Go Public - Danna Solihin3, Annisa Setiyo Wati1 Mardiana 2 (EKONOMIA, 2020)
Annisa Setiyo Wati, Analysis of Return On Investment (ROI) at PT. Kino Indonesia Tbk Before and After Go Public (under the guidance of Ms. Mardiana as advisor I and Mrs. Danna Solihin as mentors II).            The purpose of this study is to know and analyze the growth of PT. Kino Indonesia Tbk Return On Investment (ROI) before and after going public.The theoretical basis used in this study is Sujarweni (2016:6) argues that the definition of management accounting is "Management accounting is one of the fields of accounting that studies how to produce financial information for management which will then be used for decision making". Rudianto (2013: 192) argues that the Return on Investment (ROI) is: "Return On Investment (ROI) is a ratio that shows the return (return) on the amount of assets used in the company. ROI is also a measure of management effectiveness in managing its investment".            The analytical tool in this study uses financial ratios, namely the profitability ratio (Return On Investment), and the ratio of growth rates. The results showed that the Return on Investment (ROI) of PT. Kino Indonesia Tbk prior to going public for the 2014-2015 period had increased, as indicated by the number 46.77% whereas growth in the period 2015-2016 before going public PT. Kino Indonesia Tbk decreased to -32.72% and growth increased after going public in the 2016-2017 period and the 2017-2018 period, as indicated by the 2016-2017 Return on Investment (ROI) growth rate of -38.65% and the 2017-2018 period of 23, 37%.